THE ROLE OF ART-PEDAGOGY IN THE DEVELOPMENT OF CHILDREN’S CREATIVITY AND ARTISTIC CULTURE - Qoraboyeva Sevinch Shuhrat qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: In this article, the development of creative abilities of preschool children from the first years is recognized as one of the modern approaches to improving the quality of preschool education, and the development of creativity of preschool children with the help of art pedagogy is described as a pedagogical problem, and the issues of art pedagogy in the development of children's creativity and artistic culture are highlighted.